Rosette Guitar Quartet : Proses Kreatif Melalui “Youtube” Sebagai Pasar Industri Musik Digital - Danang Sandy Tyas (STIE PGRI Dewantara Jombang, 2021)
The existence of YouTube as a promotional medium is utilized by the Rosette guitar quartet in presenting a musical performance presented with the creation and production in the form of audio-visual uploaded via YouTube social media. With the growing need and dependence of the public on YouTube channels, YouTube's function has begun to grow no longer as a medium of entertainment alone, YouTube has also begun to function as a reference, promotion, and even existence for certain groups such as artists, musicians and indie artists who are not exposed to television media. and those that already exist in the entertainment world. The purpose of this study is to describe the creative process of the Rosette Guitar Quartet in facing the digital music market. This research uses a qualitative approach. Qualitative research focuses on data not numbers, and seeks to answer questions rather than test hypotheses. The result of this research is the creative process of the Rosette Guitar Quartet in utilizing YouTube as a digital music industry market through the presentation of music in audio-visual form.